(untitled) (Acta Scientiarum. Biological Sciences, 2015)
We tested the hypothesis that the contribution of the nestedness component is higher in environments with more similar features (lentic or lotic), whereas the contribution of the turnover component is higher in environments with more dissimilar features (lotic vs. lentic). To this end, we partitioned beta diversity of the Oligochaeta community into 12 environments of the Upper Paraná River floodplain. We recorded 986 individuals of 17 taxa. Through Redundancy Analysis, we observed a differentiation between lentic and lotic habitats both by environmental features as species composition. Our hypothesis was partially supported, because in environments with more similar hydrological characteristics, we observed a greater contribution of the nestedness component only in lentic environments, whereas in lotic environments, the turnover component showed a higher value. Moreover, when analyzed the different environments (lentic vs. lotic), we noticed a very similar contribution of both components. Some species were more frequent, as A. pigueti and P. americana, while others were exclusive to some environments (N. bonettoi and H. aedeochaeta). We evidenced the importance of each component in structuring Oligochaeta community, nonetheless, in a different way between environments with more similar (nestedness to lentic and turnover to lotic) or dissimilar (almost the same contribution of both) features.